Anti-Influenza Activity of 6BIGOE: Improved Pharmacological Profile After Encapsulation in PLGA Nanoparticles - Schroeder, Josefine; Westhoff, Jan; Vilotijević, Ivan; Werz, Oliver; Hoeppener, Stephanie; Löffler, Bettina; Fischer, Dagmar; Ehrhardt, Christina (International Journal of Molecular Sciences, 2025)
Influenza A virus (IAV) infections continue to threaten public health. Current strategies, such as vaccines and antiviral drugs, are limited due to their time-consuming development and drug-resistant strains. Therefore, new effective treatments are needed. Here, virus-supportive cellular factors are promising drug targets, and the encapsulation of candidate substances in poly(D,L-lactic-co-glycolic acid) (PLGA) nanoparticles (NPs) is intended to improve their bioavailability. This study investigates the potential of the indirubin derivative 6-bromoindirubin-3′-glycerol-oxime ether (6BIGOE), a glycogen synthase kinase 3 (GSK-3)β inhibitor, for its potential to regulate IAV replication in vitro. The effects of 6BIGOE-loaded PLGA NPs on cell metabolism were assessed by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) and lactate dehydrogenase (LDH) assays in A549 and Calu-3 cells. Viral replication and spread were monitored in various IAV-infected cell lines in the absence and presence of free and 6BIGOE-loaded PLGA NPs via plaque assays and Western blot analysis. The encapsulation of 6BIGOE in PLGA NPs resulted in reduced negative side effects on cell viability while maintaining antiviral efficacy. Both encapsulated and free 6BIGOE exhibited antiviral activity, potentially through GSK-3β inhibition and the disruption of key signaling pathways required for viral replication. The data indicate 6BIGOE, particularly after encapsulation in NPs, as a potential candidate for further investigation and development as an antiviral agent to treat IAV infections.
CRIS-Team Scopus Importer:2025-05-23
Keywords: antiviral; glycogen synthase kinase 3 (GSK-3); indirubin; influenza A virus (IAV); nanoparticles (NPs); poly(D; L-lactic-co-glycolic acid) (PLGA)

Bromo-substituted indirubins for inhibition of protein kinase-mediated signalling involved in inflammatory mediator release in human monocytes - Bachmann, Vivien; Schädel, Patrick; Westhoff, Jan; Perić, Milica; Schömberg, Fritz; Skaltsounis, Alexios Leandros; Höppener, Stephanie; Pantsar, Tatu; Fischer, Dagmar; Vilotijević, Ivan; Werz, Oliver (Bioorganic Chemistry, 2024)
Targeting protein kinases that regulate signalling pathways in inflammation is an effective pharmacological approach to alleviate uncontrolled inflammatory diseases. In this context, the natural product indirubin and its 6-bromo-substituted analogue 6-bromoindirubin-3 -glycerol-oxime ether (6BIGOE; 1) were identified as potent inhibitors of glycogen synthase kinase-3β (GSK-3β). These inhibitors suppress the release of pro-inflammatory cytokines and prostaglandins (PG) from human monocytes. However, indirubin derivatives target several protein kinases such as cyclin-dependent kinases (CDKs) which has been a major concern for their application in inflammation therapy. Here, we report on a library of 13 5-bromo-substituted indirubin derivatives that have been designed to improve potency and target selectivity. Side-by-side comparison of reference compound 1 (6BIGOE) with 5-bromo derivatives revealed its isomer 2 (5BIGOE), as the most potent derivative able to supress pro-inflammatory cytokine and PG release in lipopolysaccharide-stimulated human monocytes. Analysis of protein kinase inhibition in intact monocytes, supported by our in silico findings, proposed higher selectivity of 1 for GSK-3β inhibition with lesser potency against CDKs 8 and 9. In contrast, 2 supressed the activity of these CDKs with higher effectiveness than GSK-3β, representing additional targets of indirubins within the inflammatory response. Encapsulation of 1 and 2 into polymer-based nanoparticles (NP) improved their pharmacological potential. In conclusion, the 5- and 6-brominated indirubins 1 and 2 as dual GSK-3β and CDK8/9 inhibitors represent a novel concept for intervention with inflammatory disorders.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Bromoindirubins; Cyclin-dependent kinases; Cytokines; Glycogen synthase kinase-3β; Inflammation; Monocytes; Polymer-based nanoparticles; Prostaglandins

Vaterite-based in situ surface modification and process-dependent biocompatibility of laser sintered polypropylene - Schlicht, Samuel; Campbell, Jack Charlie; Weber, Alexander Christian; Westhoff, Jan; Volodkin, Dmitry; Fischer, Dagmar; Drummer, Dietmar; Vikulina, Anna (Journal of Materials Research and Technology, 2024)
Polypropylene (PP) rapidly gains scientific attention as fatigue-resistant and lightweight tissue repair and implant material, while emerging laser-sintering based methods for PP processing further allow unlimited versatility of PP specimens and often reduced numbers of process steps, substituting traditional manufacturing approaches. Generally, PP is considered biocompatible for a variety of medical applications while showing superior long-term stability, however, thermoplastic processing of polypropylene may induce the formation of cytotoxic degradation products, necessitating its cytotoxicological assessment. In the present study, PP specimens have been fabricated using warm, quasi-isothermal and complementary cold, non-isothermal powder bed fusion (PBF), allowing processing PP at ambient powder bed temperature of 25 °C for minimizing thermal exposure and the formation of decomposition products. The surface of manufactured specimens has been modified with hybrid coatings consisting of mesoporous inorganic microcrystals of vaterite laden with model biomacromolecules, i.e., fluorescently labelled dextran, demonstrating the stable coating and attachment of dextran-loaded vaterite crystals independent of the applied PBF processing regime. Vaterite coating is degradable and enables the opportunity to endow the surface of PP with sustained release functionalities. Both coated and uncoated specimens demonstrated excellent biocompatibility independent of the applied processing regime, as evaluated in an ex ovo shell-less hen’s egg model.
Keywords: powder bed fusion; additive manufacturing; vaterite; drug release; hen’s egg model